ANTAGONISM DUBOIS IN MODERN CONDITIONS - A. Zaitsev; N. Kotelevskaia; O. Boichenko; A. Nikolishin (Український стоматологічний альманах, 2018)
The article presents the results of research indicators of caries and periodontal tissue status. Part of the research carried out by employees of the Department of Therapeutic Dentistry Higher State Established Educatiuon of Ukraine «Ukrainen Medical Dental Academy». Other studies taken from the literature. Based on these studies we analyzed the compatibility of carious lesions and inflammatory diseases periodontal tissues.